P27 Blood neutrophil levels in IPF patients are significantly associated with quantitative radiological progression of fibrosis. (11th November 2022) - Achaiah, A; Fraser, E; Saunders, P; Hoyles, R; Benamore, R; Ho, LP
Abstract : Background: Idiopathic pulmonary fibrosis (IPF) is a progressive fibrotic lung disease with poor prognosis. Large retrospective clinical studies have demonstrated association between blood leukocytes levels and mortality, but correlation with progression of fibrosis has not been fully explored. Objective: Determine if blood leukocyte levels are associated with progression of fibrosis in IPF using automated CT Lung texture analysis. Methods: We performed a retrospective analysis of an IPF cohort (n=164) seen in the Oxford ILD Service between 2016–2021. Non-contrast high resolution computed tomography scans were analysed using the CALIPER (Computer-Aided Lung Informatics for Pathology Evaluation and Rating) CT algorithm. CALIPER total lung fibrosis (TLF) and pulmonary vessel volume (PVV) scores were calculated at baseline and follow-on CT timepoints. We used Pearson (r) correlation to determine association between blood leukocytes (monocytes, neutrophil and lymphocytes measured <4 months from 1st CT) with baseline CALIPER TLF, CALIPER PVV, and FVC% and TLCO% closest to CT. Leukocyte association with disease progression was explored using a multivariate Cox regression fitting a model around increase in fibrosis >10%/litre of lung. Results: Mean age of cohort 75.1 SD± 7.9 y, 90% male. Median FVC 76.6% (IQR 66.6–91.2), TLCO 56.9% (49.5–67.0). Neutrophil level correlated with TLF (r=0.208, p=0.007) and PVV (r=0.259, p=0.001). There was significant correlation between neutrophils and upper and middle zone fibrosis and PVV, but weaker correlation with FVC% (r=-0.127, p=0.029) and TLCO% (r=-0.104, p=0.079). Neither monocyte or lymphocyte level correlated with TLF, PVV, FVC% or TLCO%. 71 cases underwent repeat CT; mean time 28.9 m (±16.7) between CTs. In multivariate analysis adjusted for age, gender and% change in CALIPER lung volume, PVV and leukocyte levels, neutrophil count demonstrated significant association with progression of TLF [HR 2.66, 95%CI, 1.35–5.25, p=0.005]. See table 1 . Conclusion: In our cohort, neutrophil levels showed stronger correlation with CALIPER fibrosis and PVV scores, and radiological progression of fibrosis (within 3 years). Neutrophil levels could indicate patients at greater risk of progression of fibrosis in IPF.